Empowered with Wings: Professional Development for Supporting Children's Social and Emotional Wellbeing in South-West Queensland. (20th October 2016) - Cartmel, Jennifer; Smith, Kerry; Miller, Debbie
Abstract : Wings: Social and emotional wellbeing in the early years is a professional development programme designed to assist educators in early years services to improve outcomes for children. It uses a strengths-based approach and supports educators to understand the impact of their interactions with children and to use communication strategies, such as descriptive feedback, to develop children's capacities. These strategies are used to help children recognise their strengths and build their ability to self-regulate and manage their own social and emotional wellbeing. This paper reports on the outcomes of the Wings programme introduced into early childhood services in rural and remote south-west Queensland, Australia, through the Community Wellbeing Project run by the Pathways to Resilience Trust in partnership with Anglicare Southern Queensland. Preliminary findings indicate the Wings programme successfully enhanced the confidence and knowledge of early years educators engaged in promoting children's social and emotional wellbeing.